Kontribusi perceived usefulness, perceived ease of use dan perceived security terhadap behavioral intention to use aplikasi JAKET - Onita Sari Sinaga; Fenny Krisna Marpaung; Reni Shinta Dewi; Acai Sudirman (Forum Kerjasama Pendidikan Tinggi, 2021)
The development of the use of information technology in various fields provides added value to society in an advanced development process. The existence of the use of information technology has entered all sectors, especially when it has penetrated the transportation sector. The success of technology acceptance is reflected in the user's ability to apply this technology in their daily lives without encountering several obstacles. The substance of this study is to determine the effect of perceived usefulness, perceived ease of use, and perceived security on the behavioral intention to use the JAKET application. The sample in this study amounted to 120 respondents who were determined by convenience sampling approach. Data analysis using the SPSS application by displaying the results of data processing through test research instruments with validity and reliability, multiple regression analysis, the coefficient of determination, and hypothesis testing. The research results prove that only perceived ease of use and perceived security have a significant effect on behavioral intention to use. As for the effect of perceived usefulness on behavioral intention to use, the results are not significant.